Melanoma - risk factors and prevention strategies - Magiera, Barbara; Rybak, Jakub; Magiera, Karol (Journal of Education, Health and Sport, 2023)
Introductions and purpose: Melanoma is a malignant skin cancer, characterized by a very high rate of increase in the number of cases. The aim of this study is to analyze the key modifiable and non-modifiable risk factors associated with the development of melanoma and to discuss existing prevention strategies. Materials and methods: A literature review was conducted using the "PubMed" database with the keywords "melanoma", "melanoma risk factors", "melanoma primary prevention" and “melanoma secondary prevention”. State of knowledge: Melanoma risk factors can be divided into two groups: modifiable and non-modifiable. The main modifiable factor is UV radiation. Non-modifiable risk factors include: genetic factors, phenotypic characteristics, age, gender, and the presence of melanocytic nevi. UV radiation is responsible for the incidence of 60-70% of melanomas. Reducing exposure to risk factors is crucial in primary prevention, while self-examination and medical examination are important in secondary prevention. Summary: Despite the very high rate of increase in the number of cases, morbidity and mortality associated with melanoma can be effectively reduced by adhering to the principles of primary and secondary prevention. Patient education is crucial to reduce exposure to modifiable factors and increase vigilance against new skin lesions.